Macam-Macam Konsep Kurikulum - Wantono; Sari Hermawati (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2025)
The curriculum is the main device in education that functions as a guideline for learning and the learning process as well as an evaluation tool for learning. There are four approaches in the curriculum, namely academic curriculum, humanistic curriculum, social reconstruction, and technology. Each has different characteristics, ranging from mastery of knowledge, personal development, social problem solving, to the utilization of technology. All four approaches have their own advantages and disadvantages, but in practice, they have not been optimal. An integrative approach that combines all four is deemed relevant in the modern era because it can create holistic, contextual, and learner-centered learning. This integration supports the formation of intelligent, character-building individuals who are prepared to face the challenges of the 21st century.